MiR‐125b regulates side population in breast cancer and confers a chemoresistant phenotype. Issue 10 (16th August 2013) - Wang, Hong‐Jiang; Guo, Ying‐Qiu; Tan, Guang; Dong, Lei; Cheng, Lei; Li, Ke‐Jun; Wang, Zhong‐Yu; Luo, Hai‐Feng
ABSTRACT Resistance to chemotherapy is a major obstacle for the effective treatment of breast cancer and is partially due to the presence of drug resistant stem cell‐like side population (SP). Previous studies have shown elevated miR‐125b is associated with chemoresistance and metastasis; however, the relationship between miR‐125b and SP cells remains unknown. In this study, we isolated and characterized SP cells in a panel of breast cancer cell lines and primary cancer cells from breast cancer patients. SP cells showed cancer stem cells (CSCs) properties, including self‐renewal, resistance to chemotherapy and high expression of stem cell markers. The percentage of SP cells was higher in chemotherapy resistant patients compared to that in chemotherapy responsive patients (5.8 ± 2.4% in non‐responsive patients vs. 1.2 ± 0.5% in responsive patients, P = 0.012). Importantly, SP cells had higher level of miR‐125b than NSP cells and the elevated miR‐125b expression in chemoresistant cancer cells were due to high percentage of SP cells. Overexpression of miR‐125b correlated with an increase in tumor SP and CSC property, whereas knockdown of miR‐125b correlated with decreased incidence of SP. In addition, miR‐125b overexpression in breast cancer cells induced epithelial–mesenchymal transition (EMT)‐like cellular marker alteration, suggesting a potential mechanism of miR‐125b in the regulation of cancer stem‐like SP cells. Taken together, these results suggest an important role for miR‐125b in breast cancer chemoresistance by maintaining cancer stem‐like SP fraction, and raise the possibility that miR‐125b may be a significant prognostic response marker for cancer therapy. J. Cell. Biochem. 114: 2248–2257, 2013. © 2013 Wiley Periodicals, Inc.